Study the Association of Uromodulin Gene rs13332878 with Chronic Kidney Disease - Albayati, Ahmed Saad; Al Jowari, Suha Abdulkhaliq (Iraqi Journal of Science, 2023)
Uromodulin is the most abundant protein ordinary excreted in urine which could be used as a biomarker to diagnose kidney diseases. However, evidence suggests that it regulates salt transport, protects against urinary tract infection and kidney stones, and has a role in kidney damage and innate immunity. This study aimed to understand the association of uromodulin gene rs13332878 with chronic kidney disease. More than 100 people were selected for the study and the samples collected from the under study subjects were divided into two groups. 70 chosen subjects were under the dialysis with kidney failure, and aged between 18-88 years. The second group included 30 samples from healthy individuals, used as control. One of the ways used to identify the genotype was the tetra-primers amplification refractory mutation system–polymerase chain reaction (ARMS–PCR). Regarding the results of SNP (rs13332878), there were three genotypes: GG, CG and CC. Genotype GG was shown in the size 288bp, genotype CG was shown in the size 288+577bp, whereas genotype CC was shown in the size 577bp. The results of frequency genotypes that appeared for GG, GC and CC were 74.29%, 17.14% and 8.57% respectively in patients. Whereas in the control, the frequency of genotypes was GG 3.33%, GC 16.67% and CC 80%. It was observed that less than 1 odds ratio meant that the genotypes were to be considered as a preventive factor. While more than 1 OR meant that the risk had increased (P-value 0.01). No significant differences for the genotypes GC were found when comparing patients and the control groups (P> 0.01). So, we can conclude that there was an association between SNP (rs13332878) of uromodulin with kidney disease and genotype GG should be considered a risk factor while CC genotype represents a preventive factor.